RANCANG BANGUN APLIKASI MONITORING DAN EVALUASI PENYALURAN DANA SOSIAL DI DINAS SOSIAL KABUPATEN SUMBAWA BERBASIS WEB - Teguh Hamdala; Shinta Esabella (Program Studi Informatika Universitas Teknologi Sumbawa, 2020)
This study aims to design and build a Monitoring and Evaluation (Monev) Application for Distribution of Social Funds in the Web-Based Sumbawa Regency Social Service in order to assist the Social Service in the Field of Facilitation and Social Security Facilitation in reporting or evaluating the conditions of social funds as well as monitoring changes recipient of social funds in Sumbawa Regency. Data collection methods used in this study are interviews, observation and literature studies and using spiral methods as a method of software development. This application was built using the Hypertext Propocessor (PHP) programming language and MySQL database as a Database Management System (DBMS). This application can help the Social Service in the Field of Facilitation of Protection and Social Security in reporting or evaluating the conditions of social funds while also carrying out the process of monitoring changes in recipients of social funds in Sumbawa Regency